(untitled) (Journal of Hama University, 2022)
There are many ways which help to prevent patients from developing infections in the hospital during the treatment, thus protecting them from risk factors and accelerating their recovery,Therefore, it was necessary to shed light on one of these factors that cause hospital infections, which is the failure of the operating elements to follow the correct steps for surgical hand washing, as these elements must wash their hands in accordance with international policies for a period of no less than 5 minutes, following a correct scientific method before any surgical procedure in order to prevent the transmission of infection and thus preserve the health of patients. the aim of this studying was to know the extent of commitment of the health staff members in the Operations Department at Hama National Hospital to apply the correct steps for surgical hand washing. a descriptive cross sectional study was performed using a sample of 50 surgical assistants in operating department of different categories. These categories are resident doctors in the department, nurses holding a bachelor’s degree, and nurses holding a diploma. A special questionnaire was used to collect data that includes demographic information and a set of closed questions that are answered with a yes or no answer. The findings of this study showed that 62% of participants didn’t adhere to the correct steps for surgical hand washing due to their lack of knowledge of the correct steps for surgical hand washing. on the other side the study showed that74% of participants consider surgical hand washing procedure is important to avoid infections ,this study suggest to activating the role of infection control program coordinators in hospitals and urging them to follow up on the elements’ adherence to infection control policies, including commitment to apply the correct steps for surgical hand washing.